Designing The Information System for Data Collection of Covid-19 Symptoms for Indonesian Citizens - Thamrin Thamrin; Delsina Faiza; Ahmaddul Hadi; Khairi Budayawan; Geovanne Farell; Igor Novid (Universitas Negeri Padang, 2021)
Information systems are the result of rapidly emerging technological developments because human needs as information users of technology are very strong and rapid. Begin with the very rapid growth of computer technology, computers such as smartphones, tablets, notebooks and others are limited in scale. This small computer device must be connected to the Internet so that it can be used properly. And the information system plays its role as a provider of information that computer users want to access when the computer device is linked to the Internet. The information system developed in this paper is the Citizen Data Collection Information System, this system was created using the YII Framework. The YII framework uses the MVC method which makes it easier to develop a Citizen Data Collection Information System. With this Information System, information about the latest condition of the residents can be easily accessed. So that the Kelurahan, Kecamatan, RW, and RT will have the latest information about their residents and easily anticipate if needed. In the development of this system, it has staged such as literature study, observation, interviews, analysis, design, testing, and implementation. The conclusion is that this information system can carry out the desired function when it is implemented.